The Theoretical Bases for Determining the Fiscal Space of Territorial Communities in a Decentralized Environment - Kvasnіi Oksana R. (Problemi Ekonomiki, 2019)
The article carries out a critical analysis of the scientific definitions of the fiscal space as an economic category. The approaches to interpretation of the concept of «fiscal space» are systematized; the resource-expenditure, targeted, quantitative and effective approaches are allocated. The essence, advantages and disadvantages of each of these approaches are substantiated. The necessity and relevance of transferring the concept of «fiscal space» to the local level is proved, which is connected with the reform of inter-budgetary relations, financial decentralization, formation of united territorial communities, and necessity for ensuring their ability to function. The author’s own definition of the fiscal space of territorial community is proposed as a totality of economic processes and financial interactions of the community’s economic entities, localized within its limits, which are the result of an active fiscal policy to increase the tax potential of the territory and strengthen the target orientation of the local budget expenditures aimed at improving the life of the territorial community and its level of financial viability. The main features of the fiscal space of territorial community and the properties of fiscal space as an economic system are allocated. It is defined that the fiscal space is formed by three elements of public finance: budget revenues, expenses, and debt. It is argued that the fiscal space of the territorial community is feasibly to consider as a combination of the tax potential and the potential for costs reduction without compromising the public interest in order to strengthen their target orientation.